Chemical and physical properties of biomass burning aerosols and their CCN activity: A case study in Beijing, China - ZJ Wu; Zheng, J.; Y. Wang; Shang, D. J.; Du, Z. F.; Zhang, Y. H.; Hu, M. (Science of the Total Environment, 2017)
Biomass burning emits large amounts of both trace gases and particles into the atmosphere. It plays a profound role in regional air quality and climate change. In the present study, an intensive campaign was carried out at an urban site in Beijing, China, in June 2014, which covered the winter wheat harvest season over the North China Plain (NCP). Meanwhile, two evident biomass-burning events were observed. A clear burst in ultrafine particles (below 100 nm in diameter, PM1) and subsequent particle growth took place during the events. With the growth of the ultrafine particles, the organic fraction of PM1 increased significantly. The ratio of oxygen to carbon (O:C), which had an average value of 0.23 +/- 0.04, did not show an obvious enhancement, indicating that a significant chemical aging process of the biomass-burning aerosols was not observed during the course of events. This finding might have been due to the fact that the biomass-burning events occurred in the late afternoon and grewduring the nighttime, which is associated with a low atmospheric oxidation capacity. On average, organics and black carbon (BC) were dominant in the biomass-burning aerosols, accounting for 60 +/- 10% and 18 +/- 3% of PM1. The high organic and BC fractions led to a significant suppression of particle hygroscopicity. Comparisons among hygroscopicity tandem differential mobility analyzer (HTDMA)-derived, cloud condensation nuclei counter (CCNc)-derived, and aerosol mass spectrometer-based hygroscopicity parameter (kappa) values were consistent. The mean. values of biomass-burning aerosols derived from both HTDMA and CCNc measurements were approximately 0.1, regardless of the particle size, indicating that the biomass-burning aerosols were less active. The burst in particle count during the biomass-burning events resulted in an increased number of cloud condensation nuclei (CCN) at supersaturation (SS)= 0.2-0.8%. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: activation; Biomass burning; boreal forest; ccn; Chemical composition; cloud condensation nuclei; combustion; Environmental Sciences & Ecology; high-resolution; hygroscopic growth; Hygroscopicity; measurements; north china; particle hygroscopicity; secondary organic aerosol; size-resolved